(889) Lectures in Program Evaluation and Review Technique (PERT) محاضرات في أسلوب تقييم ومراجعة البرامج (PERT) - اماني عمر (معهد التخطيط القومي, 2026)
تتناول المذكرة أسلوب "بيرت" (PERT) وهو تقنية رياضية وإحصائية تُستخدم لتقييم ومراجعة البرامج والمشاريع الكبيرة. يركز المحتوى على كيفية تخطيط المشاريع المعقدة من خلال تقسيمها إلى "أحداث" و"أنشطة" مرتبطة بجدول زمني، مع شرح مفصل لكيفية رسم الشبكات البرمجية وتحديد "المسار الحرج" الذي يحدد أقصر مدة ممكنة لإنهاء المشروع، بالإضافة إلى حساب أوقات السماح (Slack Time) التي تساعد المديرين في توقع التأخيرات المحتملة وتوزيع الموارد بشكل فعال.كما jستعرض الجوانب التحليلية لتقدير تكاليف المشروع وضغط الجدول الزمني (Crashing) لتقليل مدة التنفيذ بأقل تكلفة ممكنة، مستخدماً في ذلك نماذج البرمجة الخطية (Linear Programming). وتتضمن المذكرة تطبيقات عملية لتقدير الاحتمالات الإحصائية لإنهاء المهام في مواعيدها المحددة بناءً على ثلاثة تقديرات زمنية (متفائل، وأكثر احتمالاً، ومتشائم)، مما يجعلها دليلاً شاملاً لمحللي المشاريع لضمان التنسيق الأمثل بين الموارد المتاحة والجدول الزمني المستهدف. study covers the PERT (Programme for Terminology and Research) methodology, a mathematical and statistical technique used to evaluate and review large programs and projects. The content focuses on how to plan complex projects by breaking them down into "events" and "activities" linked to a schedule. It provides a detailed explanation of how to draw software networks and identify the "critical path," which determines the shortest possible project completion time. It also covers calculating slack time, which helps managers anticipate potential delays and allocate resources effectively. Furthermore, it explores the analytical aspects of project cost estimation and schedule crashing to minimize execution time and costs, using linear programming models. The document includes practical applications for estimating the statistical probabilities of completing tasks on schedule based on three time estimates (optimistic, most likely, and pessimistic), making it a comprehensive guide for project analysts to ensure optimal coordination between available resources and the target schedule.